Hubungan pola konsumsi, perilaku merokok, dan risiko gastritis pada mahasiswa: analisis perbandingan jenis kelamin - Habibah Abidin; Farras Jihan Nabilah; Desti Ambar Wati (Poltekkes Kemenkes Aceh, 2026)
Background: Gastritis is inflammation of the gastric mucosa associated with irregular eating patterns, consumption of high-risk foods, and smoking behavior. University students are a vulnerable group due to the academic demands and lifestyle factors that influence their dietary habits. Previous research has stated that 56.2% of college students experience gastritis, but gender-based analysis is still limited.Objectives: This study analyzed the relationship between dietary patterns, risky food consumption, and smoking behavior with gastritis incidence among students at Universitas Pendidikan Indonesia, with sex-based comparisons.Methods: This study employed a quantitative analytic design with a cross-sectional approach, conducted between September and November 2025. A total of 100 students were selected using purposive sampling methods. Data were collected using online questionnaires covering eating patterns, consumption of high-risk foods, smoking behavior, and history of gastritis. The questionnaire was validated by two experts and pilot-tested on 20 respondents. Data were analyzed using the Mann-Whitney U test for sex differences and Spearman’s correlation after normality testing with the Kolmogorov-Smirnov test (p<0,005).Results: Most students had irregular eating patterns, with an average of two meals per day. Significant sex differences were found in carbohydrate portion size (p=0,001) and smoking behavior (p<0,001) and smoking behavior (p<0,001). Consumption of spicy foods was significantly associated with the incidence of gastritis (p=0,005).Conclusion: Irregular eating patterns and consumption of spicy food are the main factors associated with gastritis among university students, with notable sex differences. Therefore, nutrition education and gender-sensitive health promotion programs in university settings must be strengthened.